Tenun wastewater treatment using membrane bioreactor (MBR) with external ceramic microfiltration - Nor Liyana, Mohd (2012)
Tenun industry in Malaysia is one of the small traditional businesses but it has contributed in increase economic resources of Malaysia. Tenun was popular at the East Coast of Malaysia and it is an inherited skill from generation to generation. In Pahang, tenun has been established as Tenun Pahang Royal and it is an exclusive handicraft where it difficult to obtain in other countries. The productions of tenun handicraft product require high of skill in managing and operate the tenun machine. The color consume in making the colorful tenun textile is one of the most important part in producing the attractive to fill the demands. Besides, the color utilize high chemical contain where it can contribute to pollution. Most of the tenun industries do not provide any pre-treatment before discharge the tenun wastewater from industries. Due to this action, it has cause pollution to the environment surrounding the industrial area. The preliminary study shows that the wastewater from tenun textile used to color the yarn contains suspended solids and high concertration of dyes whether organic or inorganic. This study explores the use of aerobic membrane bioreactor process in removing the suspended solid due to coloring process from the tenun wastewater. In the other hand, the effect of COD, BOD and color concentration were studied based on due to hydraulic retention time. The data collected shows the effectiveness of membrane in dye removal that contains in the wastewater by using the membrane bioreactor technology.